THE ROLE OF VITAMIN D IN MUSCLE PERFORMANCE AND INJURY PREVENTION IN ATHLETES - Kornelia Kaźmierkiewicz; Martyna Chojnacka; Marta Ewelina Lis; Ewa Ciechańska; Kornel Kapuśniak; Weronika Suszczyńska; Katarzyna Rumianek-Fidziukiewicz; Zuzanna Lasota; Weronika Domańska (International Journal of Innovative Technologies in Social Science, 2025)
Vitamin D, a fat-soluble secosteroid, is traditionally associated with the regulation of calcium and phosphate metabolism; however, its role also extends to muscle function and immunity. The active form of this vitamin, 1,25-dihydroxyvitamin D, acts through receptors in muscle tissue (VDR), stimulating protein synthesis and regulating intracellular calcium balance. In this way, it supports proper muscle strength and structure. Vitamin D deficiency disrupts these mechanisms—leading to atrophy of type II muscle fibers, impaired mitochondrial function, and reduced muscle strength and bone density. The result is an increased susceptibility to injury, slower regeneration, and a prolonged recovery period, particularly in athletes. Studies confirm that vitamin D deficiency is common even among physically active individuals, especially those who train indoors or have limited sun exposure. Regular vitamin D supplementation effectively raises serum 25(OH)D levels, reduces the risk of stress fractures (by more than 75% in some groups), and improves functional outcomes, especially when combined with appropriate training. However, in individuals with adequate vitamin D levels, additional supplementation does not provide further performance benefits. Regular monitoring of 25(OH)D concentration and an individualized approach to supplementation—taking into account risk factors such as skin type, geographic latitude, and training environment—are essential. While some methodological limitations are present in the scientific literature, the available evidence suggests that maintaining adequate vitamin D levels plays a key role in preventing injuries and supporting both bone and muscle health among physically active individuals.